Increasing The Quality Of Lecturer Service Through Strengthening Servant Leadership, Empowerment, Work Motivation, And Job Satisfaction: An Empirical Study Approach using Path Analysis and SITOREM Analysis - Anwar, Syairi; Hardhienata , Soewarto; Sunardi, Oding (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
The purpose of this study is to find ways and strategies to improve service quality by analyzing the influence of other variables on service quality. Other variables are Servant Leadership, Empowerment, Work Motivation, and Job Satisfaction. Furthermore, it was found that ways and strategies to improve the quality of lecturer services found were used as recommendations to related parties, namely the Head of BPSDM of the Ministry of Transportation. This research method uses the path analysis method to see the direct and indirect effects between variables and the SITOREM method to determine the order of priorities and recommendations for improvements that need to be made. The research population was 327 Higher Education Lecturers of the Ministry of Transportation. The research sample was 181 respondents determined by the Taro Yamane formula. Sampling is done by Proportional Random Sampling. The results of the path analysis (1) there is a direct positive influence of servant leadership on service quality of = 0.265, (2) there is a direct positive influence of empowerment on service quality of = 0.143, (3) there is a direct positive effect of work motivation on service quality of = 0.192 , (4) there is a direct positive influence of job satisfaction on service quality of = 0.151, (5) there is a direct positive influence of servant leadership on work motivation of = 0.245, (6) there is a direct positive influence of empowerment on work motivation of = 0.228, (7) there is a direct positive influence of servant leadership on job satisfaction of = 0.268, (8) there is a direct positive influence of empowerment on job satisfaction of = 0.245, (9) there is an indirect positive influence of servant leadership on service quality through work motivation of = 0.339, (10) there is an indirect positive influence of empowerment on service quality through work motivation of = 0.0242, (11) there is an indirect positive influence of servant leadership on service quality through work motivation of = 0.345, (12) there is an indirect positive influence of empowerment on service quality through work motivation of = 0.246. The results of SITOREM analysis show that there are indicators of service quality variables, servant leadership, empowerment, work motivation and job satisfaction that are prioritized for improvement, including indicators (1) Accountability, (2) Listening, (3) Organizational Procedure), (3) Achievement, (4) Progress, (5) Working Condition, (6) Responsibility, (7) Status, (8) Confession, (9) Compensation, (10) promotion, (11) Salary, (12) work colleague, (13) Supervision, (14) Job condition, (15) Jobs, (16) involves, (17) Communication, (18) reward, (19) responsiveness, (20) tangible.